A new method to build the (inverse) distance ladder - Camarena, David; Marra, Valerio (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. The cosmic distance ladder is the succession of techniques by which it is possible to determine distances to astronomical objects. Here, we present a